Diazepam Promotes Translocation of Human Constitutive Androstane Receptor (CAR) via Direct Interaction with the Ligand-Binding Domain - Skoda, Josef; Dusek, Jan; Drastik, Martin; Stefela, Alzbeta; Dohnalova, Klara; Chalupsky, Karel; Smutny, Tomas; Micuda, Stanislav; Gerbal-Chaloin, Sabine; Pavek, Petr (Cells, 2020)
The constitutive androstane receptor (CAR) is the essential regulator of genes involved both in xenobiotic and endobiotic metabolism. Diazepam has been shown as a potent stimulator of CAR nuclear translocation and is assumed as an indirect CAR activator not interacting with the CAR cavity. In this study, we sought to determine if diazepam is a ligand directly interacting with the CAR ligand binding domain (LBD) and if it regulates its target genes in a therapeutically relevant concentration. We used different CAR constructs in translocation and luciferase reporter assays, recombinant CAR-LBD in a TR-FRET assay, and target genes induction studied in primary human hepatocytes (PHHs), HepaRG cells, and in CAR humanized mice. We also used in silico docking and CAR-LBD mutants to characterize the interaction of diazepam and its metabolites with the CAR cavity. Diazepam and its metabolites such as nordazepam, temazepam, and oxazepam are activators of CAR+Ala in translocation and two-hybrid assays and fit the CAR cavity in docking experiments. In gene reporter assays with CAR3 and in the TR-FRET assay, only diazepam significantly interacts with CAR-LBD. Diazepam also promotes up-regulation of CYP2B6 in PHHs and in HepaRG cells. However, in humanized CAR mice, diazepam significantly induces neither CYP2B6 nor Cyp2b10 genes nor does it regulate critical genes involved in glucose and lipids metabolism and liver proliferation. Thus, we demonstrate that diazepam interacts with human CAR-LBD as a weak ligand, but it does not significantly affect expression of tested CAR target genes in CAR humanized mice.
Keywords: hepatocyty; Cell Line; Male; ligandy; drug interaction; Cell Proliferation; Receptors, Cytoplasmic and Nuclear; reportérové geny; cytochrome P450; Ligands; Adult; CAR; dospělí; Diazepam; mužské pohlaví; Hepatocytes; proteinové domény; Animals; lidé; konstitutivní androstanový receptor; ženské pohlaví; játra; Humans; zvířata; gene regulation; diazepam; myši; buněčné linie; proliferace buněk; Protein Transport; NR1I3; Liver; Genes, Reporter; Female; receptory cytoplazmatické a nukleární; Mice; Protein Domains; lidé středního věku; transport proteinů; Constitutive Androstane Receptor; Middle Aged